A case study on the electrical energy auditing and saving techniques in an educational institution (IMCO, Sohar, Oman). (March 2022) - Al Rashdi, Salim Ahmed; Sudhir, C.V.; Basha, J. Sadhik; Saleel, C Ahamed; Soudagar, Manzoore Elahi M.; Yusuf, Abdulfatah Abdu; El-Shafay, A.S.; Afzal, Asif
Abstract: Due to the rapid economic growth and rising Oman population, Oman's annual energy demand has increased by approximately 9%. This percentage signifies that there is a considerable expansion of industries and other manufacturing sectors as the population increases. A study of the energy audit of International Maritime College Oman (IMCO) was conducted to determine the opportunities to save energy efficiency costs, which will be reflected positively in reducing the operational costs of the buildings. In this study, the annual energy consumption of IMCO buildings was simulated using DesignBuilder software. The validation of the simulation results was performed using monthly electricity consumption billing records, with an average of 7.4% during all months. Two strategies were proposed to manage energy consumption: replacing the traditional fluorescent lamp with a LED lamp light control and installing window solar films that are able to control solar heat. The simulation results of the two strategies showed 16% and 7.6% reductions, respectively, in energy consumption. A cost analysis of the findings was performed and showed a payback period of less than 2.5 years for both proposals.